MAKSUD DAN WAKTU “MALAM AL-QADAR” Kajian terhadap QS al-Qadar (97) - Zainal Arifin (Journal Analytica Islamica, 2016)
Surah al-Qadr led to the study of the noblest work at night which is better than 1000 months. Is the most noble job by al-Qadr? This study assessed for the relations with the textual verses contextual happened. In addition to position the traditions that have been the foundation reinforcement and support. This paper seeks to contribute to the goal is to restrict the study of the patterns of logic language of the Quran, formulated the concept of the value system and traces the history of social life is happening at that moment. This paper found that is not always tafsir bi al-matsur is the best interpretation. Tarawih prayer alone is good so that every individual can repeat memorizing the Koran which he had memorized. The conclusion of this paper is based on language, interpretation, hadith and historical facts: that the night of al-Qadr was glorious meaning, the intention is to lower the Koran in life. The time there are four: (1) the decline in the Koran night and it only happens once in the period of the Prophet Muhammad, (2) but the spirit happened all the time and it was better than 1000 months. Who understand the Koran and practicing it (anytime and anywhere, inside or outside of Ramadan, at night or during the day) he had to get al-Qadr is better than 1000 months. (3) full month of Ramadan; (4) in the odd nights at the end of Ramadan.